2013
DOI: 10.1111/dme.12229
|View full text |Cite
|
Sign up to set email alerts
|

Early‐pregnancy maternal vitamin D status and maternal hyperglycaemia

Abstract: Aims To estimate the association between serum 25-hydroxyvitamin D concentrations and maternal hyperglycaemia (post-load glucose concentration ≥ 7.5 mmol/l). Methods Pregnant women (n = 429; 61% black, 36% obese, 45% smokers) enrolled in a cohort study at <16 weeks gestation. Non-fasting blood samples were assayed for serum 25-hydroxyvitamin D at enrolment. At 24–28 weeks gestation, maternal hyperglycaemia was determined using a 50-g 1-h oral glucose challenge test. Results A total of 67% of women had 25-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…In our study, we detected no difference in 25(OH)D levels between smokers and non‐smokers. However, similar interactions have been described between maternal 25(OH)D status and gestational diabetes . The authors of these studies postulated a role for the antiinflammatory and antioxidant effects of vitamin D that might mediate the association between 25(OH)D and gestational diabetes.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, we detected no difference in 25(OH)D levels between smokers and non‐smokers. However, similar interactions have been described between maternal 25(OH)D status and gestational diabetes . The authors of these studies postulated a role for the antiinflammatory and antioxidant effects of vitamin D that might mediate the association between 25(OH)D and gestational diabetes.…”
Section: Discussionmentioning
confidence: 67%
“…Through its role in the regulation of immune cells, it protects β cells from detrimental immune attacks and even enhances their function (27). The role of VD in the development of pregnancy-related diabetes has been the subject of numerous studies, and it has been shown that VD deficiency affects the altered glucose homeostasis during pregnancy (28). Eight observational studies have recently been conducted to study the association of VD with gestational diabetes mellitus (GDM), and reported an inverse relationship between VD status in early pregnancy and risk of gestational diabetes (23).…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Two large studies published after these meta‐analyses did not observe significant inverse associations between 25(OH)D concentration and GDM . Another recent study suggested that maternal smoking may modify the relationship between 25(OH)D and maternal hyperglycaemia (measured instead of gestational diabetes because of small numbers), such that in smokers a significant inverse association was observed between 25(OH)D concentration and hyperglycaemia, but no association was found in non‐smokers . A potential mechanism, proposed by Tomadi et al ., suggests that vitamin D may work to reduce the risk of hyperglycaemia in smokers, because of increased inflammation, a risk factor for GDM .…”
mentioning
confidence: 95%
“…Another recent study suggested that maternal smoking may modify the relationship between 25(OH)D and maternal hyperglycaemia (measured instead of gestational diabetes because of small numbers), such that in smokers a significant inverse association was observed between 25(OH)D concentration and hyperglycaemia, but no association was found in non‐smokers . A potential mechanism, proposed by Tomadi et al ., suggests that vitamin D may work to reduce the risk of hyperglycaemia in smokers, because of increased inflammation, a risk factor for GDM . Although these mechanisms are speculative, if interactions between smoking and 25(OH)D are verified, a large public health impact could be realised if it were possible to identify such at‐risk women for targeting interventions.…”
mentioning
confidence: 99%